The effect of Bafa Wubu of Tai Chi on college students’ anxiety and depression: A randomized, controlled pilot study - Zhang, Jianwei; Gao, Tianming; Li, Yameng; Song, Zhenshao; Cui, Meize; Wei, Qiuyang; Chen, Zaihao; Peng, Fang; Lyu, Shaojun (Frontiers in Physiology, 2023)
Objective: This pilot study aimed to explore the mechanism of the effects of Bafa Wubu of Tai Chi (BWTC) on anxiety and depression in college students using resting-state functional magnetic resonance imaging (RS-fMRI). Methods: Eighteen college students (5 males and 13 females) with anxiety and depression met the study criteria and were randomly divided into an experimental group (aged 24.20 ± 4.07 years) and a control group (aged 22.50 ± 5.95). The experimental group received an eight-week BWTC intervention five times/week for 60 min/session. The control group maintained normal daily life without any exercise intervention. These students were assessed using RS-fMRI scans, the self-rating anxiety scale (SAS), and the self-rating depression scale (SDS). Spearman correlation analysis was used, and statistical significance was defined as a two-sided p-value of < 0.05. Results: After the intervention, the SAS and SDS scores of the BWTC group significantly reduced (p = 0.002; p = 0.001). Compared with the control group, the fALFF values of the right middle frontal gyrus, orbital part (Frontal_Mid_Orb_R) (p = 0.043), right inferior occipital gyrus (Occipital_Inf_R) (p = 0.003), and right middle temporal gyrus of the temporal pole (Temporal_Pole_Mid_R) (p = 0.003) in the BWTC group increased significantly; the fALFF values of the left middle frontal gyrus (Frontal_Mid_L) (p = 0.001) and right supplementary motor area (Supp_Motor_Area_R) (p = 0.010) in BWTC group decreased significantly. The fALFF values of Frontal_Mid_Orb_R were significantly positively correlated with the SDS score (r = 0.852, p = 0.015) and the fALFF values of Frontal_Mid_L were significantly negatively correlated with the SAS score (r = -0.797, p = 0.032). Conclusion: In this pilot study with college students, BWTC alleviated anxiety and depression, potentially through modulating activity in the Frontal_Mid_L and Frontal_Mid_Orb_R, respectively.